PROBLEMS IN REFORMATION OF MEDICAL HEIs IN KYRGYZSTAN - Ainazik M. Omurzakova (International Journal of Innovative Technologies in Social Science, 2020)
The article deals with problems of medical HEIs in the Kyrgyz Republic, related to transition from the model of directive management to a new educational policy. Integration of Kyrgyz education to international modern standards in terms of ensuring quality of education.